(untitled) (PUBMET, 2022)
The article addresses scholars’ information behaviour and how they use technology to acquire information in three areas of their work: teaching, research, and administrative responsibilities. Research in information behaviour highlights fundamental problems concerning information availability, recognisability, and context (Jones et al., 2017). On the other hand, it can respond to information diffusion by demonstrating the perspective of information transmission and sharing (Vilar, 2014). Because context is so important, it is likely that scholars in different fields of science will have distinct informational habits when it comes to finding knowledge (Canary, McPhee, 2011; Yu & Zhou, 2015.). An assumption in the model of information space (I-Space) is that dissemination of information is weaker as the targeted audience is broader (Boisot, 1995). The aim of our study was to find which communication channels academics utilize to find and share knowledge. Are they those targeting a broader audience, i.e. formal-explicit communication, or those targeting a narrower one, i.e. informal-tacit communication? Our questionnaire, which included 125 academics from Croatian public polytechnics, aimed to find how respondents received knowledge in the three primary areas of work through various communication methods. Nine possible statements were presented for each domain and scored on a seven-point Likert scale. The domains included personal level, informal and formal groups, and public modalities for disseminating information, such as the Internet and institutional intranets, social networks, and cloud technologies. With Cronbach’s alpha coefficient value we can confirm that the set of statements in questions has sufficient internal consistency and is reliable for further processing. Considering a large number of channels for each area of activity, a reduction was made through Principal Component Analysis (PCA), with the aim of determining new factors to find the latent component in various communication channels and to discover which type of communication is most represented in each domain and with a distinction between science field. We discovered that academics typically locate material for teaching purposes in a narrower scope and in a more direct form inside communication channels, whereas information for research purposes is obtained in a broader scope and in a more explicit form. Although explicit in nature, information collection and dissemination through administrative operations takes place within a smaller scope in either formal or informal methods (Goes, 2015). Our factor analysis shows a distinction between social and technical domains of science in terms of how scholars collect material for administrative task. This work is part of a larger study aimed at determining the mechanisms of information diffusion within an academic institution utilizing information space model.